Analisis Kepuasan Pengguna Aplikasi Lazada Masyarakat Penajam Menggunakan Metode Pieces Framework - Jakaria Jakaria; Joy Nashar Utamajaya (STMIK Budi Darma, 2022)
Lazada is one of the most popular mobile-platform-based e-commerce in Indonesia today with more than 100 million downloads. During the current COVID-19 pandemic, the Lazada application can be a very helpful application to meet user needs without having to leave the house. In this study, evaluation activities were carried out on a Lazada information system to assess whether the Lazada application used was able to meet the needs of its users, namely Lazada application users. In conducting an analysis or evaluation of a system, it is carried out with an analytical model. Data collection uses the PIECES Framework method, data calculation uses a Likert scale, and determines the average satisfaction. Based on the calculation results, it is known that the PIECES method can be seen in almost every variable getting results (PUAS).